Measuring the effectiveness of volatility auctions (2018)
We propose a method for event studies based on synthetic portfolios that provides a robust data-driven approach to build a credible counterfactual. The method is used to evaluate the effectiveness of volatility auctions using intraday data from the Colombian Stock Exchange. The results indicate that the synthetic portfolio method provides an accurate way to build a credible counterfactual that approximates the behavior of the asset if the auction had not taken place. The main results indicate that the volatility auction mitigates the volatility of the asset, but its effect on liquidity and trading activity is ambiguous at best.